Effect of Presoaking Methods to Break Seed Dormancy in Indigenous Purple Passion Fruits. - Abaho, Darius (Kabale University, 2024)
The indigenous purple passion fruits are grown in Uganda and internationally, for consumption or for juice, which is often added to other fruit juices, to enhance aroma and has nutritional importance, as a source of vitamin A in copious amounts and fair amounts of B 1 and B2 in the human diet. It is also a possible export crop of juice and syrup for flavoring. The challenge with passion fruit production is that their seeds are characterized by hard seed coats which inhibit the embryo from accessing water and oxygen. This leads to delay in germination and failure of seeds to germinate in seed beds. This study aimed to assess the best presoaking method to break the dormancy of passion fruit seeds. The study tested the use of hot water, citric acid, and sucrose solution as measures to break seed dormancy of passion seeds in comparison with control seeds (untreated). After the seed treatment, seeds were sown in the seedbed in 2 replications The data was collected, and analysis was done with the aid of SPSS software to perform one-way ANOV A and Microsoft Excel, to identify significant differences in germination percentage among the seed treatment methods. Seeds soaked in citric acid had the highest germination percentage at 53.33% and the lowest germination percentage in control seeds at 2.22%. There were significant differences in germination percentage among treated seed samples with a p-value greater than 0.05 (one¬way ANOV A). Based on the findings, the three methods tested in the study i.e. using citric acid, use of sucrose solution, and hot water proved very effective methods of breaking seed dormancy of passion fruits. Citric acid was the most effective method, characterized by a high germination percentage. There is a need to try citric acid on seeds of other species of passion fruit.